The Application of Nanobubble Technology in Hydroponic SWU-01 to Increase Dissolved Oxygen Concentration and Lettuce Plant Growth - Asep Yusuf; Chay Asdak; Mimin Muhaemin; Eza Zahrotul Fuadah; Sophia Dwiratna; Muhammad Achirul Nanda; Anto Tri Sugiarto; Hilman Syaeful Alam (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Hydroponic model SWU-01 is a new hydroponic system innovation that regulates watering automatically and independently by utilizing gravity and Archimedes' law. Dissolved oxygen concentration in SWU-01 is only around 3-4.2 mg/L. DO values can be increased by applying nanobubble technology. Ultrafine bubble or nanobubble is a gas bubble in a liquid that has a diameter of <200 nm. The purpose of this study was to determine the effect of nanobubble on dissolved oxygen concentration and growth of lettuce plants cultivated with SWU-01 hydroponics. The experiment used a one-factor randomized complete block design, namely intermittent administration of nanobubble for 15 min every 3 day (P1) and 7 days (P2), and without nanobubble (P0l). The results obtained based on the ANOVA test at the 5% level with the Least Significant Difference (LSD) follow-up test, namely the parameters of fresh weight and number of leaves of lettuce P1 significantly different from P0 and P2, and no significant differences were found in root length, canopy width, and plant height. The P1 treatment is more effective in increasing dissolved oxygen concentration, leaf count, and fresh weight of lettuce produced in lettuce cultivation using the SWU-01 hydroponic system. Keywords: Dissolved oxygen, Hydroponics, Lettuce, Nanobubbles, Plant growth.